2015
DOI: 10.1371/journal.pone.0131705
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Epileptogenesis after Kainate-Induced Status Epilepticus in C57BL/6J Mice: Evidence from Long Term Continuous Video-EEG Telemetry

Abstract: The C57BL/6J mouse as a model of seizure/epilepsy is challenging due to high mortality and huge variability in response to kainate. We have recently demonstrated that repeated administration of a low dose of kainate by intraperitoneal route can induce severe status epilepticus (SE) with 94% survival rate. In the present study, based on continuous video-EEG recording for 4-18 weeks from epidurally implanted electrodes on the cortex, we demonstrate that this method also induces immediate epileptogenesis (<1-5 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
122
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 70 publications
(136 citation statements)
references
References 70 publications
(136 reference statements)
6
122
1
Order By: Relevance
“…In a recent study, high frequency of spike-wave discharges in EEG in animals with kainate-induced seizures were associated with central apnea 29 . Recent studies using the kainic acid model have emphasized that the frequency of generalized tonic-clonic seizures during SE determines its severity and outcome 6;8;30 . In the future, carefully designed studies to monitor cardiac and respiratory functions during experimental SE are needed to clarify the relationship between convulsive seizures and death and to elucidate the underlying neurobiological mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, high frequency of spike-wave discharges in EEG in animals with kainate-induced seizures were associated with central apnea 29 . Recent studies using the kainic acid model have emphasized that the frequency of generalized tonic-clonic seizures during SE determines its severity and outcome 6;8;30 . In the future, carefully designed studies to monitor cardiac and respiratory functions during experimental SE are needed to clarify the relationship between convulsive seizures and death and to elucidate the underlying neurobiological mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…These models are important tools in understanding the mechanisms of epileptogenesis 6;8 . These models have limitations when used to study the pathophysiology of SE.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the SE induced by repeated low dose of kainate (i.p) in C57BL/6J mouse model produce severe SE, and continuous video-EEG confirmed that they develop epilepsy in less than 5 days (Puttachary et al, 2015b). A similar rapid epileptogenesis has been reported in the mouse pilocarpine model (Mazzuferi et al, 2012).…”
Section: Severity Of Status Epilepticus Determines Epileptogenesismentioning
confidence: 98%
“…Interestingly, the clinical trial guidelines recommend ~5 min to intervene in the case of continuous convulsive seizures (Dodson et al, 1993; Lowenstein et al, 1999; Shinnar et al, 2001; Seinfeld et al, 2016). In chemoconvulsant animal models, it has been known that a minimum of 10 min of convulsive SE is sufficient to cause brain injury and to induce temporal lobe epilepsy (Nairismagi et al, 2004; Puttachary et al, 2015b). …”
Section: Severity Of Status Epilepticus Determines Epileptogenesismentioning
confidence: 99%
See 1 more Smart Citation